2021
DOI: 10.1002/bbb.2216
|View full text |Cite
|
Sign up to set email alerts
|

OSiD: opening the conceptual design of biobased processes to a context‐sensitive sustainability analysis

Abstract: Biobased production has been promoted as an alternative to fossil‐based production to mitigate climate change. However, emerging concerns over the sustainability of biobased products have shown that tensions can emerge between different objectives and concerns, like emission reduction targets and food security, and that these are dependent on local contexts. Here we present the Open Sustainability‐in‐Design (OSiD) framework, the aim of which is to integrate a context‐sensitive sustainability analysis in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Palmeros-Parada et al ( 2021 ) concluded that sustainability can be defined or evaluated through the identification of relevant issues or indicators in the socioeconomic and environmental interaction of the industry, crop fields, population, public policies, etc., to measure the level of sustainability which is based on stakeholder engagements but mainly within the application of established framework of the 2030 sustainable development agenda and its indicators, goals, and objectives.…”
Section: Transition Of Sugar Industry To Sustainabilitymentioning
confidence: 99%
“…Palmeros-Parada et al ( 2021 ) concluded that sustainability can be defined or evaluated through the identification of relevant issues or indicators in the socioeconomic and environmental interaction of the industry, crop fields, population, public policies, etc., to measure the level of sustainability which is based on stakeholder engagements but mainly within the application of established framework of the 2030 sustainable development agenda and its indicators, goals, and objectives.…”
Section: Transition Of Sugar Industry To Sustainabilitymentioning
confidence: 99%
“…Involving local stakeholders in the set-up or design of biobased value chains can be a way of dealing with the many uncertainties surrounding the set-up of global biobased value chains (Rist et al, 2007); local producers often have valuable knowledge about land management, their natural environment and the associated biomass (Sumane et al, 2018). Such knowledge is important in understanding how to design biobased value chains that are sustainable (Parada et al, 2021). Involving local biomass producers can thus be expected to have both epistemic and moral benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these findings, we provide conclusions related to the case study and the followed methodology for a more sustainable biobased production. Note that the followed methodology and its contribution to the field of sustainable biobased production has been recently discussed by Palmeros Parada et al [22].…”
Section: Introductionmentioning
confidence: 99%